Efficiency and Effectiveness of Government Expenditure on Health in The Districts of East Nusa Tenggara Province - Julius Innosensius Beon; Achmad Solihin (MASI Mandiri Edukasi, 2026)
Local governments have attempted to allocate health budgets in accordance with constitutional mandates; however, the life expectancy remains relatively low. This study examines the efficiency and effectiveness of public health spending in 22 districts/cities in East Nusa Tenggara Province (NTT) during 2017–2024. Efficiency was assessed using Data Envelopment Analysis (DEA) with Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) assumptions. Effectiveness was analyzed through panel data regression from the Central Statistics Agency (BPS) for 2017–2024, lagged by 1 year, and using a fixed effects model. The DEA findings indicate that most regions have not achieved optimal technical efficiency, largely due to geographic constraints and scale inefficiencies. Meanwhile, the regression results indicate that government health spending does not significantly affect life expectancy. In contrast, GDP per capita and access to clean water exhibit significant positive effects. However, household health spending exhibits a significant negative relationship, indicating a significant financial burden for individuals. These findings highlight the importance of reallocating health budgets, prioritizing capacity building for medical personnel, and strengthening financial protection mechanisms through expanding health insurance coverage.